Problem solving: How can we help students overcome cognitive difficulties - Liberato Cardellini (OmniaScience, 2014)
The traditional approach to teach problem solving usually consists in showing students the solutions of some example-problems and then in asking students to practice individually on solving a certain number of related problems. This approach does not ensure that students learn to solve problems and above all to think about the solution process in a consistent manner. Topics such as atoms, molecules, and the mole concept are fundamental in chemistry and instructors may think that, for our students, should be easy to learn these concepts and to use them in solving problems, but it is not always so. If teachers do not put emphasis on the logical process during solving problems, students are at risk to become more proficient at applying the formulas rather than to reason. This disappointing result is clear from the outcomes of questionnaires meant to measure the ability to calculate the mass of a sample from the number of atoms and vice versa. A suggestion from the cognitive load theory has proved a useful way to improve students' skills for this type of problems: the use of worked out examples. The repetition after two weeks of the Friedel-Maloney test after the use of worked examples shows that students' skills significantly improve. Successful students in all questions jumped from 2 to 64%.